Income Generation: An alternative Source of Funding for Academic Libraries in Ghana: Koforidua Technical University Library in Perspective - Adu-Sarkodee, Rosemary; Asante, Edward; Akussah, Maxwell (IJRDO - Journal of Social Science and Humanities Research, 2016)
The study assesses the alternative income generation activities that academic libraries can adopt to support the funding of academic libraries in Ghana. Survey method was adopted with the use of questionnaire to gather data and information. Copies of questionnaire were distributed to the main stakeholders of the academic library, out of 200 copies of questionnaire distribute, and 121 copies were retrieved representing a response rate of 60.5% of the sample size. The study brought to light that the library has been perceived as a non-profit unit for far long, bindery and photocopying activities are among avenues for income generation and creating awareness of such activity needs urgent attention. The study recommends among others that librarians should also be given training and short courses on how to generate alternative income in the library. Besides, in showing readiness the mamgement of the parent institution should also provide the necessary tools and equipment needed for the new step.